Evaluation methods for drought tolerance of cowpeas - Watanabe, I.; Hakoyama, S.; Terao, T.; Singh, B.B. (1997)
Cowpea (Vigna unguiculata [L.| Wulp.) is primarily grown in dry regions in the tropics, particularly in sub-Saharan Africa. Drought is important among several yield-reducing factors. Nine hundred cowpea accessions from the Genetic Resources Unit of IITA were evaluated for drought tolerance in a field during the dry season at the IITA Kano Station in northern Nigeria. Some of them were retested three times in greenhouses, once in Nigeria and twice in Japan, using seedlings planted in small pots with a soil moisture level of 3% wt. Tolerance scores to drought correlated highly significantly in repeated evaluations. Two of the accessions, TVu 11979 and TVu 14914, were always highly tolerant. Merits and demerits of the two methods, a field evaluation method and a pot evaluation method, are discussed.